2010
DOI: 10.1038/eye.2010.206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retinal nerve fiber layer measured by time domain and spectral domain optical coherence tomography in optic neuritis

Abstract: Purpose To study the relationship between retinal nerve fiber layer (RNFL) thickness measurements from time domain (Stratus) and spectral domain (Cirrus HD) optical coherence tomography (OCT) in subjects with optic neuritis. Methods A total of 18 patients who had suffered monocular acute optic neuritis were imaged by a single trained operator using the Stratus-OCT (fast RNFL scan mode) and Cirrus HD-OCT (optic disc cube mode) on the same day. The relationship between RNFL thickness measurements of the two OCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
2
11
1
Order By: Relevance
“…The abnormality rate in temporal pRNFL color code in eyes with previous history of ON was 66.7% by Cirrus and 61.1% by Spectralis. The current study agrees with previous reports that eyes from patients with RRMS exhibit a significant thinning of the pRNFL and GCIPL compared with the healthy eyes [ 7 , 10 , 11 ] and that pRNFL thinning in RRMS patients typically occurs in the temporal sector [ 4 , 20 23 , 27 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The abnormality rate in temporal pRNFL color code in eyes with previous history of ON was 66.7% by Cirrus and 61.1% by Spectralis. The current study agrees with previous reports that eyes from patients with RRMS exhibit a significant thinning of the pRNFL and GCIPL compared with the healthy eyes [ 7 , 10 , 11 ] and that pRNFL thinning in RRMS patients typically occurs in the temporal sector [ 4 , 20 23 , 27 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…LCA requires tests with binary outcomes to create the model. For simplification of the analysis, white, blue, purple, and green sectors have been labeled as “normal,” and yellow and red ones as “abnormal.” For BCVA, values better than or equal to 0.3 LogMAR were labeled as normal and those worse than 0.3 as “abnormal.” BCVA was included in the model in order to provide a functional outcome that could help better define the latent class “retinal thickness change.” Temporal pRNFL was selected as it was the quadrant with a higher frequency of pRNFL thinning and abnormal results in previous studies [ 4 , 20 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6] All of them conclude that there are significant differences in RNFL thickness measurements among instruments despite a high correlation among them. OCT provides information on probable RNFL defects through comparison of the RNFL FIGURE 3.…”
Section: The Widespread Use Of Oct In the Assessment Of Thementioning
confidence: 92%
“…There are significant differences among commercially available OCT devices in RNFL thickness measurements in patients with ON and/or relapsingremitting multiple sclerosis, so that RNFL measurements cannot be directly compared. [3][4][5][6] Clinicians should be aware that measurements are generally higher with Stratus than with Cirrus, 4,5 except at thinner RNFL values, and slightly higher on Spectralis compared to Cirrus OCT. 3,6 OCT provides information on probable RNFL defects as 4 color codes through comparison of the RNFL profile with an internal age-matched normative database. Recently, Kim and associates 7 evaluated the color-code agreement between Cirrus and Stratus OCT in patients with glaucoma, and they concluded that color codes were not interchangeable.…”
mentioning
confidence: 97%
“…8,9,[11][12][13] Briefly, we used the following setting in this study: a fixation target consisting of a red ring 2°in diameter; white, 14 The points are spaced from each other by 6°. The VF is considered reliable when fixation losses were o20%, and falsepositive and false-negative errors o15%.…”
Section: Examinationmentioning
confidence: 99%